Pericardial Abscess in an Intravenous Drug User: a Case Report - Pérez-Cardona, José; Salgado, Víctor; Medina-Ruiz, Arturo; Quilinchini, José; Maldonado, Alberto (Puerto Rico Health Sciences Journal, 2008)
A 45 year old man, intravenous drug user, without history of systemic illness, presented with fever, chills and an anterior left thorax pulsatile mass. Echocardiogram showed an anterior mediastinal fluid collection with no apparent pericardial communication and without evidence of endocarditis. Chest tomography revealed a large left anterior mediastinal abscess with multiple pulmonary abscesses. Percutaneous aspiration and blood cultures were positive for Staphylococcus aureus. Surgical drainage with pericardiectomy was done.